Design and emulation of an SDN network with opendaylight to improve QoS in a peruvian financial institution - Roncal, Juan David Indigoyen; Paulino, Christian Ovalle (Institute of Advanced Engineering and Science, 2025)
This study presents the design and emulation of a software-defined networking (SDN) architecture using the OpenDaylight controller to enhance the quality of service (QoS) in a Peruvian financial institution. The main objective is to overcome limitations of traditional networks, including high latency, limited bandwidth, and packet loss, which hinder the efficiency of financial services. The proposed SDN architecture was implemented and tested through simulations in the Eve-NG platform, where key performance parameters—latency, throughput, and packet loss—were measured. Results demonstrated significant improvements, with latency reduced by up to 40%, stable throughput maintained at 10 Mbps across all branches, and a noticeable reduction in packet loss. These outcomes validate the feasibility of adopting SDN in financial environments to support critical services and ensure operational continuity. Furthermore, the findings emphasize SDN’s role in modernizing network infrastructures, improving user experience, and aligning local financial institutions with international technological trends. Future research may explore alternative SDN controllers, scalability in larger topologies, and integration with emerging technologies such as network function virtualization (NFV).